Choose the point-slope form of the equation below that represents the line that passes through the points (-3, 2) and (2, 1).
y + 3 = -5(x - 2)
y - 2 = -5(x + 3)
y + 3 = -(x - 2)
y - 2 = -(x + 3)

Q: Choose the point-slope form of the equation below that represents the line that passes through the points (-3, 2) and (2, 1).
y + 3 = -5(x - 2)
y - 2 = -5(x + 3)
y + 3 = -(x - 2)
y - 2 = -(x

+ 3)

A: The answer is 2y - x + 1 = 0
Solution:
m = (-2 + 3)/(-3 + 5) ;
= 1/2 ;
y + 3 = 1/2 (x + 5) ;
2y + 6 = x + 5 ;
2y - x + 1 = 0

Choose the point-slope form of the equation below that represents the line that passes through the points (-3, 2) and (2, 1). y + 3 = -5(x - 2) y - 2 = -5(x + 3) y + 3 = -(x - 2) y - 2 = -(x + 3)

There are no comments.